HPLC Determination of Sugar Contents Based on Harvest Season in Almonds [Prunus dulcis (Mill.) D.A. Webb.] - FIKRET BALTA, M.; DOGAN, A.; EREZ, M.E.; Battal, P.; Yoruk, I.H. (Asian Journal of Chemistry, 2010)
This study presents in comparison with harvest seasons sugar contents in 18 promising almond selections [Prunus dulcis (Mill.) D.A. Webb.] from Balikesir (western Anatolia, Turkey). Their majority had kernel weight over one gram since large kernel is a desired fruit characteristics for almond breeding efforts. Nuts of almond genotypes were collected at two seasons based on their harvest times. The harvest seasons were late August for 8 promising genotypes and early September for other 8 genotypes. Sugar contents were detected by HPLC. Selections harvested in late August and early September averagely contained 2.19-2.31 g/100 g sucrose, 0.68-0.92 g/100 g maltose, 2.09-1.82 g/100 g glucose and 4.08-3.41 g/100 g fructose. Sugar contents of selections did not differ by harvest season statistically. Whereas, significant differences were found among selections for each harvest season. In addition, the mean sugar was fructose in 12 genotypes, sucrose in 4 genotypes and glucose in one genotype.